Odpowiedzi

2010-02-28T20:50:00+01:00
A)2+3x-4+5x=8x-2
b)-(3X-4) + 6 +(2x-1) =-3x+4+6+2x-1=-x+9
c)- ( 2x - 1 - 2 x + y)=1-y
d)- ( 2 X - 1 ) -(4 X - 5 )+ 6 x =6
2010-02-28T20:56:06+01:00
A) 2+3x-4+5x = 0
3x+5x=-2+4
8x = 2 /:8
x = 0,25

b) -(3x-4) + 6 + (2x-1) = -3x+4+6+2x-1=0
-3x+2x=-4-6+1
-1x = -9 /:-1
x=9

c) -(2x-1-2x+y) = -2x+1+2x-y = 0
-y = -1 /:-1
y=1

d) -(2x-1) - (4x-5) +6x = -2x+1-4x+5+6x = 0
-2x-4x+6x=-1-5
0x=-6 Nie ma rozwiązania

e) (3x+4) - (2x - (3x-1) +4) = 3x+4 - (2x-3x+1+4) = 3x+4 - 2x+3x-1-4 = 0
3x-2x+3x=-4+1+4
4x=1 /:4
x=0,25